32.9k views
24 votes
Rewrite each algebraic expression in an equivalent form with the fewest

number of terms possible.
a. 6(x + 7)(x + 2)
b. (2y – 5)
c. (5x + 4y)(2x - y)
d. (3x + 7)(3x – 7)
e. (t + 2) – (4t +9) – t

Rewrite each algebraic expression in an equivalent form with the fewest number of-example-1

1 Answer

12 votes

Answer:

Explanation:

The terms will be multiplied in order to get the simplified polynomials.

a. 6(x + 7)(x + 2)


6(x + 7)(x + 2)\\=6[x(x+2)+7(x+2)]\\=6(x^2+2x+7x+14)\\=6(x^2+9x+14)\\=6x^2+54x+84

The simplified form of 6(x + 7)(x + 2) is
6x^2+54x+84

b. (2y – 5)^2

Using the formula:
(a-b)^2 = a^2+b^2-2ab


=(2y)^2+(5)^2-2(2y)(5)\\=4y^2+25-20y

The simplified form is:
4y^2-20y+25

c. (5x + 4y)(2x - y)


=5x(2x-y)+4y(2x-y)\\=10x^2-5xy+8xy-4y^2\\=10x^2+3xy-4y^2

The simplified form of (5x + 4y)(2x - y) is
10x^2+3xy-4y^2

d. (3x + 7)(3x – 7)

Using the formula:
(a+b)(a-b) = a^2-b^2


= (3x)^2-(7)^2\\= 9x^2-49

The simplified form of (3x + 7)(3x – 7) is
9x^2-49

e. (t + 2) – (4t +9) – t


=t+2-4t-9-t\\=t-4t-t+2-9\\= -4t-7

The simplified form of (t + 2) – (4t +9) – t is
-4t-7

Hence,

a. The simplified form of 6(x + 7)(x + 2) is
6x^2+54x+84

b. The simplified form is:
4y^2-20y+25

c. The simplified form of (5x + 4y)(2x - y) is
10x^2+3xy-4y^2

d. The simplified form of (3x + 7)(3x – 7) is
9x^2-49

e. The simplified form of (t + 2) – (4t +9) – t is
-4t-7

User Jamaul
by
5.5k points